The identity of Félix de Azara’s “Alondras” and implications for Neotropical pipit nomenclature (Aves, Motacillidae: Anthus) - Smith, Paul; Clay, Rob P. (Zootaxa, 2021)
Félix de Azara described five species of “Alondra” in his seminal work on birds of Paraguay in 1805. Two of these are pipits Anthus: No. 146 Alondra Chií and No. 147 Alondra Correndera. Vieillot (1818) then formally described the two based entirely on Azaraʼs descriptions, respectively Anthus chii and Anthus correndera. The former has long been considered unidentifiable, though it has also been used frequently as a valid name for the Yellowish Pipit Anthus lutescens. The latter of the two names has been in valid usage since its description for the Correndera Pipit A. correndera of southern and Andean South America. In this paper we confirm that the description of No. 146 Alondra Chií is clearly identifiable and Anthus chii is the valid name for the Yellowish Pipit under the Principle of Priority, and Anthus turdinus of Merrem is a junior synonym of it. The description No. 147 Alondra Correndera is shown to refer to Ochre-breasted Pipit A. nattereri and not A. correndera as currently understood. However, the two names have been in constant usage for their respective species since their description, and thus we designate a neotype of the Correndera Pipit for current A. correndera under Article 75.6 of the International Code of Zoological Nomenclature to conserve current usage and avoid unnecessary nomenclatural confusion.